SYC - JITRIK, Noe director (LA TORRE ABOLIDA, 1989)
CONTENIDO : AUTORES MARI, ENRIQUE; FERRO, ROBERTO; VAZQUEZ VILLANUEVA, GRACIANA; BORRE, OMAR; DORRA, RAUL; FRENK, MARGIT; RUBIONE, ALFREDO; COURTINE, J.J.; LANDOWSKI, ERIC; PAZ SOLDAN, ALBA MARIA